A scoping review of digital technology applications in palliative care - YinHu Tan; Xue Liang; Wei Ming; HuiMin Xing; Yang Wang; Yan Gao (BMC Palliative Care)
Abstract Background In the current era of rapid technological development, digital technology is progressively transforming the medical field. In palliative care, its integration is an inevitable trend, offering new possibilities for improving care delivery and patient outcomes. Objective This study aimed to review the application of digital technologies in palliative care, focusing on their advantages, challenges, and measurable impacts across diverse care settings. Methods A scoping review was conducted, evaluating studies published between January 1, 2000, and August 1, 2024. Searches were performed across PubMed, CINAHL, Web of Science, Scopus, and the Cochrane Library. Original studies assessing digital interventions within palliative care settings were included. Data extraction included study design, sample size, setting, intervention type, and outcomes. Methodological quality was appraised using appropriate tools for randomized controlled trials (RCTs), non-randomized studies, mixed-methods studies, and qualitative studies. Two independent reviewers conducted the data extraction and quality appraisal, resolving disagreements through discussion. Results Twenty-four studies were included, examining digital technologies such as computer systems, virtual reality (VR), and wearable devices. Key interventions supported information provision, symptom monitoring, psychological support, and communication feedback. Digital tools demonstrated positive impacts on pain management, symptom distress, quality of life, and patient acceptability. Despite methodological strengths in most studies, limitations such as small sample sizes and inconsistent outcome measures were noted. Conclusion Digital technologies in palliative care demonstrate significant potential to improve patients’ quality of life and alleviate symptom burden through remote monitoring, real-time feedback, and personalized interventions. These innovations address limitations of the traditional biomedical model, enhancing the accessibility and overall quality of palliative care.